The Polish-Turkish war of 1620–1621: Myths and istorical reality - Valerii Stepankov; Vitalii Stepankov (Науковий вісник Чернівецького національного університету імені Юрія Федьковича. Історія, 2022)
The subject of the investigation is created by historiography, prospects of the Polish-Turkish war in its diversity of existing concepts; the major event in it turns out to be the Battle of Khotyn. The topic of the article is the study of existing myths, generated by worldviews of the authors, traditional heredity of theoretic-methodological principles of knowledge of the historical process, which used their own sympathies and antipathies, the dominant ideology in society, which distorted the reality of the causes of the war and its course. The aim of the research is, on the basis of the analysis of the sources and scientific achievements of scientists, to determine the main myths of the Polish-Turkish War, the content of each and to argument their unreliability. The methodological principles of the research are first principles of historism, objectivity, and systematicity; theoretical findings of neo-positivism, the school of «The Annals» and the «new political history». Problematic-chronological, historical-genetic, historical-comparative, historical-systemic methods, as well as methods of rational reconstruction of the text and historical-cultural attribution are used. Results. It is established the mythologization of the «triumph of Polish weapons» near Khotyn that began with the sacralization of this event in the breve of Pope Gregory XV in 1621 and 1623. The 10th of October (the next after the conclusion of the Treaty of Khotyn, when the Turkish army left its positions) was announced by them as a holiday in honor of Mary the Mother of God and the patron saints of Poland as a sign of victory. Thus, the spiritual matrix of its perception by Polish society and researchers was laid for centuries. In Ukrainian historiography, the cult of majesty of Khotyn began to form in the mid-50s of the 20th century. In Polish and Ukrainian historiographies, in spite of historical reality, the leading myths were about Porto as a brutal aggressor, who sought to «enslave» Poland and Ukraine, reach the Baltics, unite with Protestants, and defeat Austria. Simultaneously, the myth about the Polish-Lithuanian Commonwealth as a peaceful state, devoid of imperial plans to defeat Turkey and establish protection over the Danube principalities was also formed. In its turn it formed the basis for the emergence of the myth about the beginning of war not by the Polish army’s intervention in Porto in the autumn of 1620 (Tsetsor campaign) and its defeat, but by the Turkish army’s counterattack in the summer of 1621. The mythology of reticence or negative assessment of Borodavka’s activity, which played a decisive role in the formation of a powerful Cossack (Ukrainian) army, providing it with proper weapons, provant and food, and timely arrival in Khotyn, is wrong. Most Polish historians, contrary to the truth, continue to hide the key role of the Cossacks in the Battle of Khotyn, putting the Polish-Lithuanian army in the forefront. Last, perhaps most common, myth about the brilliant victory of the Commonwealth army over the Turkish invaders is as unsubstantiated as the previous ones. Conclusions. The abovementioned myths, created during the XIX–XX centuries, in Ukrainian and Polish historiographies, significantly distort the historical reality of the causes of the Polish-Turkish war, its initiator, the date of the beginning, the consequences of the Battle of Khotyn and its historical significance. Their disproof will contribute to the reconstruction of a more truthful (adequate reality) of this significant event in Central and Eastern Europe.